Quality of Life in Caregivers of ADHD Children and Diabetes Patients - Andrade, Elisa Meirelles; Geha, Laysa Minella; Duran, Paula; Suwwan, Raphael; Machado, Felipe; do Rosário, Maria Conceição (Frontiers in Psychiatry, 2016)
Introduction: Studies have shown that the presence of ADHD causes great impairment in academic, social and professional activities, as well as in the quality of life (QoL) of its patients. Similarly, the impact caused by other chronic disorders, such as diabetes, in the patient´s QoL has been emphasized in many studies. Despite its relevance, no study has yet investigated whether ADHD caregivers and diabetic patients would have similar QoL impairment. Objectives: This study was conducted in order to compare the QoL scores among ADHD caregivers and diabetic patients. Methods: We evaluated 63 caregivers of ADHD children treated at the Child and Adolescent Psychiatric Unit at the Federal University of São Paulo (UPIA-UNIFESP) and 52 adult diabetic patients. Subjects were assessed with the World Health Organization quality of Life-Breef Version (WHOQOL-BREEF), the Beck and Hamilton depression scales, and the Adult Self-Report Scale. Results: When compared to the Brazilian normative data, ADHD caregivers had significantly lower scores in the social relations and environment WHOQOL domains. ADHD caregivers and diabetic patients had similar impairment in all WHOQOL domains, except for the physical domain. Conclusion: ADHD affects the QoL of the patient’s caregiver, with similar impairment when compared to the QoL of diabetic patients. These results emphasize the need for assessing QoL of the caregivers as part of the treatment strategies. They also emphasize the need for future studies with larger sample sizes comparing how the Qol is impacted in different chronic disorders.